2009
DOI: 10.1111/j.1740-0929.2008.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermented apple diet supplementation on the growth performance and meat quality in finishing pigs

Abstract: The objective of the present study was to investigate the effect of fermented apple diet (FAD) supplementation on the growth performance and meat quality in finishing Berkshires. The FAD was made from dropped apple mixed with rice bran and barley bran. Until 81 +/- 1 kg live weight at 133 +/- 1 days, the animals were fed a growing diet, after which experimental samples were fixed at 0, 2, 4 and 6% FAD as C, T1, T2 and T3 in the finishing diets. Growth performance, ADG, ADFI and feed efficiency were improved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The fermented king oyster mushroom by-products diet had low energy (1.77 to 2.86 Mcal/kg ME) and fat (1.66 to 5.22% CF), and it seems that the CP content was affected due to the substitution of fermented king oyster mushroom by-products diet to a pig diet. Therefore, WHC increased and cooking loss decreased when fermented king oyster mushroom by-products diet was supplied to pigs for 52 d, and it is similar to results reported by Lee et al (2009) and Kang et al (2010). Animal breed, sex, age and feed are common factors influencing meat and fat color, and as mentioned, lightness (CIE L * ) of backfat surface was affected when fermented king oyster mushroom by-products diet was substituted up to 80%.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The fermented king oyster mushroom by-products diet had low energy (1.77 to 2.86 Mcal/kg ME) and fat (1.66 to 5.22% CF), and it seems that the CP content was affected due to the substitution of fermented king oyster mushroom by-products diet to a pig diet. Therefore, WHC increased and cooking loss decreased when fermented king oyster mushroom by-products diet was supplied to pigs for 52 d, and it is similar to results reported by Lee et al (2009) and Kang et al (2010). Animal breed, sex, age and feed are common factors influencing meat and fat color, and as mentioned, lightness (CIE L * ) of backfat surface was affected when fermented king oyster mushroom by-products diet was substituted up to 80%.…”
Section: Discussionsupporting
confidence: 72%
“…Fermented by-products diet sources were used, such as oyster mushroom by-products (Song et al, 2007), coproducts of apple (Lee et al, 2009) and agro by-products (Kang et al, 2010). King oyster mushroom (P. eryngii), a major mushroom produced in Korea, is rich, thereby, the use of by-products production due to increased King oyster mushroom cultivation must be considered.…”
Section: Articlementioning
confidence: 99%
“…() and Lee et al . () reported that feeding finishing pigs fermented persimmon shell or fermented off‐grade apple improved feed efficiency compared with a control group fed with ordinary feed. Other studies have also reported that organic acids improve growth performance and feed efficiency of growing pigs and piglets (Roth & Kirchgessneer ; Partanen et al .…”
Section: Resultsmentioning
confidence: 99%
“…Our result that the fermented mushroom by‐product diets decreased carcass weight is in accordance with reports by Song et al . (2007) and Lee et al . (2009).…”
Section: Discussionmentioning
confidence: 96%
“…The carcass weight was decreased by feeding supplemental 5% and 7% fermented oyster mushroom by‐product diets in pigs (Song et al . 2007) and supplemental 4% and 6% fermented apple diets in pigs (Lee et al . 2009).…”
Section: Discussionmentioning
confidence: 99%